The end of poverty? think again - Diaz, Philippe; Diaz, Philippe; Sheen, Martin 1940- (Cinema Libre Studio, 2010)
Explains how global poverty began with military conquest, slavery, and colonization that resulted in the seizure of land, minerals, and forced labor. Today's financial crisis is a direct consequence of these unchallenged policies that have lasted centuries. Features expert insights from Nobel Prize winners, acclaimed authors, university professors, government ministers, and the leaders of social movements